Tashih Recitations of the Qur’an Program in Improving the Competence of Reading the Qur'an for Students of Islamic Studies - Juanda Fhajar Afriandi; Fuady Anwar; Wirdati Wirdati (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2023)
Students of Islamic Studies as a candidate for religious teachers really need to be equipped with the ability to read the Qur’an. Religious teachers as the main person in charge of Al-Quran education for students in schools must have deep competence in the Qur'an. Among the competences of the Qur’an that must be possessed is proficiency in reading the Qur’an. That is, before an Islamic Religious Education student is assigned to become an educator at school, the student must be equipped with good competence, in the context of this study the author specifically discusses competence in aspects of reading the Qur’an. This study aims to determine the competency of reading the Qur’an for Islamic Religious Studies students in the Tashih Recitation of the Qur’an program. This study uses a quantitative method with a survey approach. The data source was taken from thirty-two informants, namely students from class 2020-2021 using a questionnaire. All data were then analyzed descriptively using the SPSS Windows version 25 quantitative analysis tool (Statistical Package for Social Scrience Version 25) Overall the results of the analysis of this study indicate that the program tashih recitation of the Qur’an is a program that supports students in improving their reading of the Qur’an, bearing in mind that there are still students who are not fluent in reading the Qur’an so this program is a solution to this problem. Then there is an increase in the ability to read the Qur’an as a result of the implementation of this program with a percentage (12.5%) to (6.25%) in the very low category, (68.75%) to (15.2%) in the low category, (9.38%) became (62.5%) in the moderate category, (6.25%) became (9.38%) in the high category and settled at (3.12%) for the very high category.